Productive Performance and Blood Biochemical Parameters of Dairy Cows Fed Different Levels of High-Protein Concentrate - Buryakov, Nikolai; Aleshin, Dmitrii; Buryakova, Maria; Zaikina, Anastasya; Nasr, Mohammed; Nassan, Mohamed; Fathala, Mohamed (Frontiers in Veterinary Science, 2022)
This study investigated the productive traits and some blood biochemical parameters of high-yielding Ayrshire dairy cows fed at different levels of Agro-Matic@LLC NGO, Russia (Agro-Matic (AM)) protein concentrate. A total of 45 high-yielding Ayrshire cows were selected and divided into three groups, each 15. The control group (0AM) fed the basal ration, while group two (1AM) and group three (2AM) fed a basal ration by replacing sunflower cake with different levels of AM (1 and 1.5 kg/head/day), respectively. Milk and blood samples were collected. The current results revealed that the ratio of rumen undegradable protein to rumen degradable protein during the period of lactation was significantly higher in the 1AM and 2AM compared with 0AM and represented (55.04, 62.14, and 41.73%), respectively. The 1AM had a beneficial effect on the digestibility of crude protein. Daily and whole fat-corrected milk (FCM 4 %) was significantly increased by 3 kg/day and 987 kg/entire lactation in 2AM when compared with 0AM, respectively. Blood total protein was significantly higher in the 1AM group (86.9 vs. 77.8 g/l) than the 0AM, while AM decreased urea concentration. Consequently, the inclusions of AM protein concentrate have a positive impact on increasing milk production and optimizing the rations in terms of the amount of non-digestible protein and the economic efficiency of milk production.